Built environment impact on people with dementia (PwD) health and well-being outcomes: a systematic review of the literature - Mangili, Silvia; Brambilla, Andrea; Trabucchi, Marco; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: The number of People with Dementia (PwD) is rising worldwide and represents a complex figure because of the changes in the cognitive sphere, altering perceptions of the Built Environment (BE). Even though the role of the built environment in the health and well-being of people it’s nowadays well known, few studies analyze and evaluate the impact of specific Architectural Features. To this end, this contribution provides a systematic review that will underline the impacts of BE on the Health and Well-being of PwD and set a matrix of the relationship with measurable outcomes. Methods: A literature review has been conducted on scientific databases. 40 studies that relate health outcomes and aspects of the built environment have been identified and organized on a comparison matrix that clearly shows the relationships between Architectural Features of BE and Health and Wellbeing Outcome. This matrix allows to identify which are the aspects that can impact on PwD as well as possible lacks. Results: Many aspects appear to be widely explored, such as BPSD or wandering. In addition, significant gaps in the relationship between recognized aspects of the built environment recognized as relevant to the well-being of people with dementia and the real impacts on health outcomes such as the location and personalization of spaces. Conclusions: This study collected the most recent studies to underline the relationship between BE and dementia, providing a set of outcomes and architectural features that can be analyzed to assess the quality of BE for PwD.